E-MODULE BASED ON RESEARCH-BASED LEARNING (RBL) ON GLOBAL WARMING MATERIAL: E-MODUL BERBASIS RESEARCH BASED LEARNING (RBL) PADA MATERI PEMANASAN GLOBAL - Nurul Fatimah; Hadi Nasbey; Upik Rahma Fitri (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
The use of learning media is crucial as it can influence the learning process of students, one of which isthe use of modules. Electronic modules (e-modules) are employed due to their interactive nature,appealing design, and ability to facilitate students' learning process. This study aims to (1) develop anelectronic module (e-module) based on Research-Based Learning (RBL) on the topic of globalwarming, and (2) determine the feasibility of the electronic module (e-module) based on Research-Based Learning (RBL) on the topic of global warming. The research method used in this study isdevelopment research utilizing the ADDIE development model. The ADDIE model consists of severalstages: Analyze, Design, Develop, Implement, and Evaluate. However, this study will be conductedonly up to the Develop stage, or product development. The e-module developed adopts a research-basedlearning model focusing on the topic of global warming, supplemented with images, videos, andanimations that are engaging and accessible from various devices.